Antagonistic Activities of Lactobacillus rhamnosus JB3 Against Helicobacter pylori Infection Through Lipid Raft Formation - Do, Anh Duy; Su, Chiu-Hsian; Hsu, Yuan-Man (Frontiers in Immunology, 2022)
Helicobacter pylori is a Gram-negative pathogen and increases the risk of stomach cancer in infected patients. H. pylori exploits lipid rafts to infect host cells. Infection triggers Lewis x antigen (Lex) and integrins clustering in lipid rafts to facilitate the adherence of H. pylori to the gastric epithelium. Considering the side effects of antibiotic therapy, lactic acid bacteria are currently one of the probiotics that offer numerous benefits to the host, as well as against H. pylori infection. In our previous study, the cell-free supernatant (CFS) derived from Lactobacillus rhamnosus JB3 (LR-JB3) at a multiplicity of infection (MOI) of 25 had the ability to attenuate the pathogenicity of H. pylori. In this study, the mucin model was established in order to simulate the gastric environment for further consider the influence of mucin on the pathogenesis of H. pylori. Our results showed that porcine stomach mucin dramatically up-regulated virulence gene expressions of H. pylori including babA, sabA, fucT, vacA, hp0499, cagA, and cagL, as well as the association ability of H. pylori and its induced IL-8 levels of infected AGS cells. The CFS derived from LR-JB3 at a MOI of 25 was able to reduce the expressions of sabA, fucT, and hp0499 of H. pylori in mucin, as well as the Lex antigen and the α5β1 integrin of AGS cells in co-cultivation condition. This inhibitory effects of LR-JB3 also suppressed lipid raft clustering resulting in attenuating Lewis antigen-dependent adherence, type IV secretion system-mediated cell contact, and lipid raft-mediated entry of VacA to host cells. In conclusion, LR-JB3 is able to affect H. pylori infection through mediating lipid raft formation of the host cells. The unknown cues secreted from LR-JB3 are valuable not only for treating H. pylori infection, but also for those diseases mediated by lipid raft signaling, such as cancer, aging, and neurodegenerative diseases.